Legal Review of the Use of Closed-Circuit Television as Electronic Evidence in Proving Criminal Acts in Indonesia - Pratiwi, Siswantari; Patmawanti, Besse (LPPM Universitas Ekasakti, 2024)
This research delves into using Closed Circuit Television (CCTV) surveillance cameras as electronic evidence in criminal proceedings in Indonesia, specifically focusing on Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 regarding Information and Electronic Transactions (ITE). The continuously advancing field of information technology, including CCTV technology, now assumes a significant role within the realm of criminal justice, particularly in detecting criminal activities. Nevertheless, a contentious issue persists surrounding the admissibility of CCTV footage as evidence in court proceedings due to the absence of explicit regulations within the Criminal Procedure Code (KUHAP) about electronic evidence. This investigation scrutinizes the legal validity of CCTV recordings as evidence, shedding light on various instances where such recordings have served as crucial evidence in criminal trials. Employing a normative legal framework, this study also evaluates the repercussions of acknowledging CCTV recordings as admissible evidence within the framework of the Indonesian criminal justice system. This study's outcomes aim to offer theoretical insights and practical contributions to the advancement of criminal law, particularly regarding evidentiary matters and the utilization of electronic evidence within Indonesia.